HUBUNGAN ANTARA SOSIALISASI GENDER DARI ORANG TUA DENGAN SIKAP REMAJA LAKI-LAKI TERHADAP KEKERASAN DALAM PACARAN - Dorothea Davita Vania; Fransisca Rosa Mira Lentari (MANASA, 2019)
Dating Violence cases, which are categorized as gender based violence are increasing from timeto time in Indonesia. Gender becomes a social characteristic that individuals learn from themoment they are born and it is primarily being socialized by parents. This gender socializationthat one receives from early age until they reach adolescence stage, can play a role in shapingone’s perception and attitude towards male and female, especially regarding romanticrelationship context, including how adolescents see the use of violence in a relationship. This studyaimed to find out the relationship between gender socialization from parents and attitude towardsdating violence in male adolescents from 16-21 years old. This study used quantitative crosssectional design. The participants were 125 male adolescents who were living in Jabodetabek withparents and were obtained using convenience sampling. In this research, Gender-relatedSocialization Scale (Raffaeli & Ontai, 2004; α = 0.859) and Attitude towards Male DatingViolence (Price & Byers, 1999; α = 0.702-0.865) were used as data collection tools. From thisstudy, we found out there is a significant correlation between gender socialization from parentsand attitude towards dating violence, attitude towards physical, and also attitude towards sexualviolence. There was no significant correlation between gender socialization from parents andattitude towards psychological violence. We also found out that participants who were currentlyengaged in a relationship have a higher score in attitude towards sexual dating violence thanparticipants who were not in a relationship.